2020
DOI: 10.1136/annrheumdis-2020-218198
|View full text |Cite
|
Sign up to set email alerts
|

Treatment adherence behaviours in rheumatic diseases during COVID-19 pandemic: a Latin American experience

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, or conduct, or reporting or dissemination plans of this research. Patient consent for publication Not required.Provenance and peer review Not commissioned; internally peer reviewed. This article is made freely available for use in accordance with BMJ's website terms and conditions for the duration of the covid-19 pandemic or until otherwise determined by BMJ. You may use, download and print the article for any lawful, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 5 publications
2
21
0
1
Order By: Relevance
“…This could be due to either inadequate supply of medications from defaulting follow-ups or poor compliance due to fear. Pineda-Sic et al 6 reported that lack of availability of medications and fear of getting sick from COVID-19 were factors for changes or suspension in medications.…”
mentioning
confidence: 99%
“…This could be due to either inadequate supply of medications from defaulting follow-ups or poor compliance due to fear. Pineda-Sic et al 6 reported that lack of availability of medications and fear of getting sick from COVID-19 were factors for changes or suspension in medications.…”
mentioning
confidence: 99%
“…As some studies have shown COVID-19 has changed the perceptions of patients with RA about their medications and the uncertainties about the safety of them (12)(13)(14). Additional to these concerns, there is an enormous amount of false information provided by the internet or social network during these days (15).…”
Section: Discussionmentioning
confidence: 99%
“…A similar survey in Mexico from a single outpatient center showed 15% (52/345) of respondents reported some form of medication nonadherence, of which 48.1% (25/52) was due to lack of drug availability and 25% (13/52) was due to concerns about contracting COVID-19 34 . In a survey from Saudi Arabia with 591 respondents who were actively taking medication prescribed for rheumatic diseases, 47.9% reported difficulty filling their prescription, 29.5% had self-altered (dose escalation, discontinuation, and reduction) their medications, and 31.9% were unable to attend rheumatology follow up visits due to local quarantine restrictions 35 .…”
Section: Impact Of Covid-19 On Patients With Inflammatory Arthritismentioning
confidence: 93%